2014
DOI: 10.6061/clinics/2014(09)10
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vivo ultrasonometric evaluation of normal and delayed fracture healing in sheep tibiae

Abstract: OBJECTIVE:To compare normal and delayed bone healing by measuring ultrasound conduction velocity across the bone callus.METHODS:A model of transverse linear and 5 mm resection osteotomies of sheep tibiae was used. Fourteen sheep were operated on and were divided into two groups of seven according to osteotomy type. The procedure was performed on the right tibiae and the intact left tibiae were used as controls. The transverse and axial ultrasound velocities were measured at 30-day intervals for 90 days, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…More recently nonlinear resonant ultrasound spectroscopy technique has been used to monitor fatigue cortical bone micro damage (22). Ultrasonometry may be used to identify bone fractures in experimental and in vivo studies and to monitor fracture healing (23)(24)(25)(26)(27). To our knowledge, we found no previous papers showing VA images of bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…More recently nonlinear resonant ultrasound spectroscopy technique has been used to monitor fatigue cortical bone micro damage (22). Ultrasonometry may be used to identify bone fractures in experimental and in vivo studies and to monitor fracture healing (23)(24)(25)(26)(27). To our knowledge, we found no previous papers showing VA images of bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, theoretically, both could be used to provide an indirect measure of those properties. It has already been demonstrated, for instance, that ultrasonometry can help diagnose the healing status of fractures and can be used as an ancillary method for that purpose, particularly when the precise situation cannot be assured by conventional methods (radiographs, CT) beyond any doubt 25,26,27,28,29,30,31.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the use of quantitative ultrasonometry during the process of fracture union in animal bones 11 12 13 14 , including certain in vivo studies 15 16 17 . The few studies that have been conducted in humans have focused on the tibia 18 19 20 21 .…”
Section: Introductionmentioning
confidence: 99%